ANALISIS KOMPARATIF NILAI KEKELUARGAAN DALAM IKLAN TEH SARIWANGI TAHUN 2017 DAN TAHUN 2025: PENDEKATAN SEMIOTIKA ROLAND BARTHES - Dina Lorenza; Fitria Yuliani (Jurnal Sarjana Ilmu Komunikasi (J-SIKOM), 2026)
This study analyzes a comparison of family values in Sariwangi Tea advertisements from 2017 and 2025 using Roland Barthes’s semiotic approach in the field of mass communication, specifically in advertising. The study aims to determine how family values are represented and how they have changed between these two advertising periods. This study is limited to an analysis of visual and verbal cues in key scenes from two commercials published on SariWangi’s official YouTube channel. Using a qualitative method, this study analyzes visual and verbal signs through three levels of meaning: denotation, connotation, and myth. The results reveal a significant transformation: the 2017 advertisement depicts a dialogic-therapeutic family model emphasizing open verbal communication, free expression of emotions, and an equal father-child relationship. In contrast, the 2025 advertisement presents a ritualistic-modern family model that highlights explicit Islamic identity, communal rituals, symbolic communication, and the re-traditionalization of gender roles. This shift reflects socio-cultural changes in Indonesian society, including the strengthening of religious identity and the re-traditionalization of family values. Theoretically, this study contributes to the field of advertising communication semiotics by demonstrating how the ideological construction of the ideal family evolves in tandem with the socio-cultural dynamics of contemporary Indonesia. Keywords: Comparative Analysis, Sariwangi Tea Advertisements, Family Values, Roland Barthes’ Semiotics, Mass Communication